The Effect of Peer Support on Behavior Menstrual Hygiene in Young Women - Agnes Monika Dewi; Kustin; Nurul Maurida; Wike Rosalini (Journal of Nursing Periodic, 2026)
Background: One of the common problems experienced by adolescent girls during menstruation is the reluctance to change sanitary pads regularly. Inadequate pad replacement can promote excessive bacterial growth and increase the risk of infection. In addition, the use of unclean or stagnant water for genital cleansing constitutes another risk factor. Poor menstrual hygiene practices commonly observed among adolescent girls include failing to change sanitary pads when they become saturated, wearing excessively tight clothing, and using fabrics that do not adequately absorb sweat. These behaviors may create a favorable environment for the proliferation of microorganisms and negatively affect reproductive health. Objective: This study aimed to determine the effect of peer support on menstrual hygiene behavior among adolescent girls. Methods: This study employed a quantitative approach with a cross-sectional design. The study population consisted of 204 female students in grades VII and VIII at SMP Negeri 3 Situbondo. A total of 136 participants were selected as the study sample using a simple random sampling technique.Data were collected through a structured questionnaire and analyzed using SPSS software to assess validity, reliability, and the relationship between variables. Results: The majority of respondents (51.47%) reported receiving good peer support, while a smaller proportion (16.18%) received poor peer support. Furthermore, most respondents (55.15%) demonstrated good menstrual hygiene behavior, whereas only 19.85% exhibited poor menstrual hygiene behavior. Statistical analysis revealed a p-value of 0.000 (< 0.05), indicating that the null hypothesis (H₀) was rejected and the alternative hypothesis (Hₐ) was accepted. Conclusion: Peer support has a significant effect on menstrual hygiene behavior among adolescent girls. Strengthening positive peer support may contribute to the improvement of menstrual hygiene practices and reproductive health outcomes among adolescents.